Comparative analysis of patient-reported outcomes in joint arthroplasty surgeries - Äärimaa, Ville; Kohtala, Karita; Mäkelä, Keijo; Karvonen, Mikko; Arimaa, Anssi; Ryösä, Anssi; Kostensalo, Joel; Kaivonen, Fanny; Laaksonen, Inari (PloS one, 2024)
This study aims to report and analyze disease-specific patient-reported outcome measure (PROM) effect size (ES) variations, in patients undergoing major arthroplasty surgery. All institution-based data of primary knee, hip, or shoulder arthroplasty patients at Turku University hospital (Finland) between January 2020 -December 2022 were collected, and treatment outcome assessed as a PROM difference between baseline and one-year follow-up. PROM ES were calculated for each patient and patient group separately, and patients with ES >0.5, were considered responders. Factors contributing to patient outcome and differences between patient groups were investigated using linear models and non-parametric methods. 2580 patients were operated (complete follow-up data on 1828 patients). 1110 (61%) of the patients were female, and mean age was 69 years (SD 10). The mean ES across all patient groups was 2.64 (SD 1.29) and the biggest ES was observed in shoulder patients and the smallest in knee patients. Smaller ES was statistically significantly associated with higher preoperative PROM, higher ASA class, and old age. The percentage of responders was highest for shoulder patients (97.7%), followed by hip patients (96.8%), and lowest for knee patients (92.5%). The observed ES for joint arthroplasty surgeries is high. However, there are significant disparities among patients with primary knee, hip, and shoulder joint arthroplasty surgery. These variations are mainly due to differences in preoperative PROM score and may be attributed to differences in patient selection. We recommend that prior to shared decision-making, preoperative scores are thoroughly reviewed with the patient, along with other patient specific factors that may influence the end result of the treatment.